2019
DOI: 10.1002/jwmg.21639
|View full text |Cite
|
Sign up to set email alerts
|

Age class dynamics of Canada geese in the Central Flyway

Abstract: Abundance of temperate-nesting Canada geese (Branta canadensis) in Central Flyway east-tier states (ND, SD, NE, KS, OK, USA) increased since the 1970s. Hunting regulations were liberalized since the mid-1990s in these states to increase harvest and reduce abundance of local populations. Because 2 age classes, juvenile and adult, are typically classified when banding, most dead-recovery band analyses of Canada geese have only considered 2 age classes to estimate survival and recovery probabilities, despite a de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
23
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(32 citation statements)
references
References 28 publications
8
23
1
Order By: Relevance
“…White, Cordes & Arnold (2013) found that substantial variation in reporting rate did not appreciably increase bias in survival probabilities. Dooley et al (2019) reported greater bias than we found in survival and recovery probabilities when two age classes were modeled for Canada geese (Branta canadensis) in the North American mid-continent, and negligible bias, similar to our findings, when three age classes were modeled. Thus, while heterogeneity in survival can be ecologically important to estimate, we do not anticipate that unmodeled heterogeneity substantially and directionally biased estimates in our application of JE models as they were based only on adult females.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…White, Cordes & Arnold (2013) found that substantial variation in reporting rate did not appreciably increase bias in survival probabilities. Dooley et al (2019) reported greater bias than we found in survival and recovery probabilities when two age classes were modeled for Canada geese (Branta canadensis) in the North American mid-continent, and negligible bias, similar to our findings, when three age classes were modeled. Thus, while heterogeneity in survival can be ecologically important to estimate, we do not anticipate that unmodeled heterogeneity substantially and directionally biased estimates in our application of JE models as they were based only on adult females.…”
Section: Discussionsupporting
confidence: 87%
“…We recommend that researchers with reported mortality probability <0.19 and low recapture probabilities continue to interpret results cautiously. While we are not aware of research explicitly evaluating bias and RMSE in JE models, our results are similar to those from recent simulation studies that explored heterogeneity using waterfowl life histories and comparable model specification with DR models (White, Cordes & Arnold, 2013;Dooley et al, 2019). White, Cordes & Arnold (2013) found that substantial variation in reporting rate did not appreciably increase bias in survival probabilities.…”
Section: Discussionsupporting
confidence: 85%
“…Most Canada goose band recovery analyses consider only 2 age classes because it is often only possible to age geese accurately as AHY or local in the field. We considered 3 age classes because geese undergo 3 behaviorally distinct life phases, and 2‐age‐class models can result in biologically improbable estimates (Heller 2010, Dooley et al 2019). Juvenile Canada geese typically have higher recovery rates (Heller 2010) and thus are expected to have lower survival than adults.…”
Section: Methodsmentioning
confidence: 99%
“…We refer to these birds as cackling geese in the text, tables, and figures, following the American Ornithologist Union's species guidelines (Banks et al 2004). Birds that observers recorded as large Canada geese were likely molt-migrant Canada geese (Abraham et al 1999;Dooley et al 2019); we retained these in the observation-level database, but did not include them in any density maps or population estimates.…”
Section: Data Processingmentioning
confidence: 99%